Intravenous lipid emulsion therapy for acute clomipramine intoxication in rats. Issue 3 (17th May 2018) - Tsuji, Takumi; Hattori, Yuji; Komori, Koji; Yoshida, Yuya; Banno, Rie; Kohno, Takeyuki
Abstract : Aim: In this study, to assess the utility of lipid emulsion (ILE) therapy as a treatment option for overdoses of lipophilic drugs, we examined the detoxification effect of ILE therapy in rats that were administered overdoses of the tricyclic antidepressant clomipramine hydrochloride (CMI). Methods: Female Wistar rats were orally administered 50 mg/kg CMI five times in 2‐h intervals to examine whether intralipos accelerated the elimination of CMI in the peripheral blood. Rats were divided into the intralipos (i.v. 2 g/kg intralipos) and placebo (i.v. saline) groups. The concentrations of CMI and desmethylclomipramine (DMCMI), a metabolite of CMI, in blood were measured over time by high‐performance liquid chromatography. We then gave the animals 100 mg/kg CMI orally to examine whether intralipos could inhibit the distribution of CMI. The CMI and DMCMI concentrations in peripheral blood, liver, and brain were measured 60 min after intralipos administration. Results: The blood concentration of CMI was significantly higher in the intralipos group than in the placebo group at 60 and 120 min. After a single administration of 100 mg/kg CMI, the ratio of the concentration of CMI in liver/serum was significantly lower in the intralipos group than in the placebo group. We also found a significantly faster elimination rate for CMI in peripheral blood in the intralipos group than in the placebo group. Conclusion: The distribution of CMI from blood to tissue was suppressed by intralipos. Therefore, ILE therapy is a promising candidate for the treatment of overdoses of lipophilic drugs. Abstract : In the intralipos group, the ratio of the clomipramine hydrochloride concentration in tissue/serum was significantly lower in liver samples and showed a tendency of being lower in brain samples when compared to the placebo group.